Reduction of Tear-Drop poikilocytes in a case of myelofibrosis following splenectomy - Chooi-Fun Leong,; Soon-Keng Cheong, (Penerbit UKM, 2006)
Myelofibrosis is a chronic myeloproliferative disorder characterised by splenomegaly, leukoerythroblastic anaemia, tear-drop poikilocytosis and marrow fibrosis. Splenectomy is indicated for patients requiring frequent transfusions or massive splenomegaly causing distressing symptoms and severe thrombocytopenia secondary to hypersplenism. A 56 year-old lady diagnosed to have primary myelofibrosis in year 2000 was referred to HUKM for further management of her increasing requirement of blood transfusion and massive splenomegaly. She has had two episodes of acute cholecytitis. Investigations done in our hospital showed that her hemoglobin level was 6.4g/dl, white cell count of 23.4x109/l, platelet count 163x109/l and peripheral blood showing leukoerythroblastic picture and tear-drop poikilocytosis. Leukocyte alkaline phosphatase score (NAP) was 184/100 neutrophils. Ultrasound of the abdomen showed massive splenomegaly with multiple gall stones. In view of the frequent transfusion requirements and symptomatic massive splenomegaly, splenectomy and cholecystectomy was performed. A review of her peripheral blood picture, post-splenectomy, showed marked reduction of the tear-drop poikilocytosis and leukoerythroblastosis. We believe that the spleen plays an important role in their formation, but the exact mechanism remains unclear